Updating the Phylodynamics of Yellow Fever Virus 2016–2019 Brazilian Outbreak With New 2018 and 2019 São Paulo Genomes - Moreira Salles, Ana Paula; de Seixas Santos Nastri, Ana Catharina; Ho, Yeh-Li; Vilas Boas Casadio, Luciana; Emanuel Amgarten, Deyvid; Justo Arévalo, Santiago; Soares Gomes-Gouvea, Michele; Jose Carrilho, Flair; de Mello Malta, Fernanda; Rebello Pinho, João Renato (Frontiers in Microbiology, 2022)
The recent outbreak of Yellow Fever (YF) in São Paulo during 2018 and 2019 has been one of the most severe in the last decades, spreading to areas with low vaccine coverage. This study aimed to assess the genetic diversity of the yellow fever virus and the mutation profile of hospitalized cases in São Paulo during the last YF outbreaks. Plasma or urine samples from acute severe YF cases (n = 56) with Polymerase Chain Reaction (PCR) positive to YFV were submitted to viral genome amplification using 11 sets of primers. Thirty-nine amplified genomes were subsequently sequenced using next generation sequencing (NGS). Sequences were aligned and analyzed to identify the viral genotype and nucleotide/amino acids substitutions. All YFV genomes belonged to genotype South American I subgroup E. Higher genetic variability was found among 2018 YFV sequences compared to those from 2019. Twenty-one non-synonymous substitutions were identified. Our findings suggest that 2018 and 2019 circulating viruses have polymorphisms that could distinguish each other. Overall, our findings provide an overview of YFV genome characterization in São Paulo State and contribute to future virological and epidemiological studies.